Mild clinical features of isolated methylmalonic acidemia associated with a novel variant in the MMAA gene in two Chinese siblings - Lin, Yiming (BMC Med Genet, 2018)
BACKGROUND: Methylmalonic acidemia (MMA) is an autosomal recessive inherited disorder caused by complete or partial deficiency of the enzyme methylmalonyl-CoA mutase (mut0 enzymatic subtype or mut– enzymatic subtype, respectively); a defect in the transport or synthesis of its cofactor, adenosyl-cobalamin (cblA, cblB, or cblD-MMA); or deficiency of the enzyme methylmalonyl-CoA epimerase. The cblA type of MMA is very rare in China. This study aimed to describe the biochemical, clinical, and genetic characteristics of two siblings in a Chinese family, suspected of having the cblA-type of MMA. METHODS: The Chinese family of Han ethnicity of two siblings with the cblA-type of MMA, was enrolled. Target-exome sequencing was performed for a panel of MMA-related genes to detect causative mutations. The influence of an identified missense variant on the protein’s structure and function was analysed using SIFT, PolyPhen-2, PROVEAN, and MutationTaster software. Moreover, homology modelling of the human wild-type and mutant proteins was performed using SWISSMODEL to evaluate the variant. RESULTS: The proband was identified via newborn screening (NBS); whereas, her elder brother, who had not undergone expanded NBS, was diagnosed later through genetic family screening. The younger sibling exhibited abnormal biochemical manifestations, and the clinical performance was relatively good after treatment, while the older brother had a mild biochemical and clinical phenotype, mainly featuring poor academic performance. A novel, homozygous missense c.365T>C variant in exon 2 of their MMAA genes was identified using next-generation sequencing and validated by Sanger sequencing. Several different types of bioinformatics software predicted that the novel variant c.365T>C (p.L122P) was deleterious. Furthermore, three-dimensional crystal structure analysis revealed that replacement of Leu122 with Pro122 led to the loss of two intramolecular hydrogen bonds between the residue at position 122 and Leu188 and Ala119, resulting in instability of the MMAA protein structure. CONCLUSIONS: The two siblings suspected of having the cblA-type of MMA showed mild phenotypes during follow-up, and a novel, homozygous missense variant in their MMAA genes was identified. We believe that the clinical features of the two siblings were associated with the MMAA c.365T>C variant; however, further functional studies are warranted to confirm the variant’s pathogenicity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12881-018-0635-4) contains supplementary material, which is available to authorized users.